Association between the centralization of dispatch centers and dispatcher-assisted cardiopulmonary resuscitation programs: A natural experimental study. (October 2018) - Ro, Young Sun; Shin, Sang Do; Lee, Seung Chul; Song, Kyoung Jun; Jeong, Joo; Wi, Dae Han; Moon, Sungwoo
Abstract: Objectives: We aimed to evaluate the associations between the centralization of dispatch centers and dispatcher-assisted bystander cardiopulmonary resuscitation (DA-BCPR) for out-of-hospital cardiac arrest (OHCA) patients. Methods: All emergency medical services (EMS)-treated adults in Gyeonggi province (34 fire departments covering 43 counties, with a population of 12.6 million) with OHCAs of cardiac etiology were enrolled between 2013 and 2016, excluding cases witnessed by EMS providers. In Gyeonggi province, 34 agency-based dispatch centers were sequentially integrated into two province-based central dispatch centers (north and south) between November 2013 and May 2016. Exposure was the centralization of the dispatch centers. Endpoint variables were BCPR and dispatcher-provided CPR instructions. Generalized linear mixed models for multilevel regression analyses were performed. Results: Overall, 11, 616 patients (5060 before centralization and 6556 after centralization) were included in the final analysis. The OHCAs that occurred during the after-centralization period were more likely to receive BCPR (62.6%, 50.6% BCPR-with-DA and 12.0% BCPR-without-DA) than were those that occurred before-centralization period (44.6%, 16.6% BCPR-with-DA and 28.1% BCPR-without-DA) ( p  < 0.01, adjusted OR: 1.59 (1.38–1.83), adjusted rate difference: 9.1% (5.0–13.2)). For dispatcher-provided CPR instructions, OHCAs diagnosed at a higher rate during the after-centralization period than during the before-centralization period (67.4% vs. 23.1%, p  < 0.01, adjusted OR: 4.57 (3.26–6.42), adjusted rate difference: 30.3% (26.4–34.2)). The EMS response time was not different between the groups (p=0.26). Conclusions: The centralization of dispatch centers was associated with an improved bystander CPR rate and dispatcher-provided CPR instructions for OHCA patients.